FUNCTIONING OF INTERNATIONAL RETAIL NETWORKS IN UKRAINE - Motsak , M.O.; Korzh , M.V. (The actual problems of regional economy development, 2023)
The article examines the peculiarities and general advantages of the functioning of international retail and trade networks. The concept of a retail trade network is defined as a general set of stationary, non-stationary, mobile, virtual subjects of retail sales of goods and services, united by a territorial feature. It has been established that international trade networks, especially in retail trade, are structures with more or less established standardized business processes, management and a special corporate climate, therefore store chains also offer a higher quality of customer service. According to the features of interaction and the form of distribution of ownership, it is proposed to distinguish: corporate trade networks; trade networks based on the distribution of privileges; trade networks based on the association of independent owners. The general advantages of functioning of international trade networks are substantiated. The essential characteristics of corporate trade networks are defined. It is substantiated that various factors influence the development of the international retail network, its needs, its structural and territorial organization, the most important of which are the following: socio-economic and demographic; geographical; urban planning; transport; organizational and technological; administrative; financial Minimizing costs, maximizing supply efficiency, maximizing supply flexibility and responsiveness, and simplifying the supply chain are identified as key value drivers for chain consumer goods retailers. It is proposed to divide all modern trading companies into: international (institutions of this network are located in several countries); national (institutions of such a network must be located in more than five regions of Ukraine); regional (institutions of such a network are located in three or four regions of Ukraine); local (branches of such networks are located in one or two regions of Ukraine). The place of international trade networks in the structure of the largest food retail operators of Ukraine by total sales area is analyzed.